Intimate Partner Violence and Its Predictors among Pregnant Women in Eastern Ethiopia: Generalized Structural Equation Modeling - Tadesse Misgana; Adisu Birhanu Weldesenbet; Dawit Tamiru; Mandaras Tariku; Dejene Tesfaye; Daniel Alemu; Berhe Gebremichael; Merga Dheresa (Hindawi Limited, 2022)
Introduction. Intimate partner violence (IPV) has a negative impact on women's physical, mental, sexual, and reproductive health. Identifying the determinant factors of IPV among pregnant women is of paramount importance to overcome its negative consequences thereby increasing the performance of women in all activities. Thus, this study applied a generalized structural equation model (GSEM) to determine the prevalence of intimate partner violence among pregnant women and its predictors in Eastern Ethiopia. Methods. A community based cross-sectional study was conducted in Kersa Health and Demographic Surveillance System (KHDSS), Eastern Ethiopia. Data were collected form a sample of 1051 pregnant women using structured questionnaires. Descript findings were presented in percentage with 95% confidence interval. The generalized structural equation model was used to determine factors associated with each domain of IPV (physical, emotional, and social violence). Adjusted odds ratio (AOR) with a 95% CI were used to declare significant factors associated with intimate partner violence. Results. The overall prevalence of IPV in the Eastern Ethiopia was 48.57% (95% CI: 45.45, 51.69). The highest intimate partner violence was observed in the sexual domain of IPV (31.6%, 95% CI: (28.8, 34.58)). In GSEM, being a farmer (AOR=0.42, 95% CI: 0.19, 0.91) was significantly associated with psychological domain of IPV. Age (AOR=0.97, 95% CI: 0.95, 0.99) and educational status (neither read nor write) (AOR=2.50, 95% CI: 1.61, 3.89) were significantly associated with physical domain of IPV. Being in medium (AOR=0.64, 95% CI: 0.46, 0.90) and rich (AOR=0.53, 95% CI: 0.36, 0.78), wealth quintiles were significantly associated with sexual domain of IPV, whereas husband controlling behavior was significantly associated with all domains of IPV. Conclusions. The magnitude of IPV among pregnant women was relatively high in Eastern Ethiopia. This finding pin a light to pay special consideration to pregnant women at each point of service delivery to alleviate consequence of IPV. Being a farmer, older ages and being in higher wealth quintiles were protective factor, whereas being uneducated increase the risk of IPV. Improving socioeconomic status and promoting legal rights of women is needed to alleviate the problem, and younger women require special attention.